Pemilihan Laboran Terbaik Penilaian Kinerja Tenaga Kependidikan Menggunakan Metode AHP - Alkodri, Ari Amir; Fitriyani, F (LPPM STIKOM Tunas Bangsa, 2024)
Educational Laboratory Staff (PLP) / Laboratories are Educational Personnel who work in managing laboratories in the context of learning, research and community service activities. Laboratory assistants consist of technicians and supervisors who must have initiative, perseverance, creativity, skills and knowledge as well as knowledge mastered by the PLP/Laboratory, helping the efficiency, effectiveness and productivity of the laboratory managed by the University. In connection with its very significant role in the performance of higher education institutions, especially in this research in the ISB Atma Luhur computer laboratory. The problem is that the Head of the Computer Laboratory and reports to campus superiors have difficulty assessing the comparison of several laboratories to determine the best performance or declining performance in each semester. The calculation of the final score uses the average value method (mean) so that all criteria are considered to have the same weight in terms of importance so that it is not possible to know which criteria are more important. The aim of the research is to apply the AHP method to select the best laboratory performance, therefore it is obtained to determine the weight of the criteria for the best laboratory assistant so that it can be used as a basis for decision making and applied by the Head of the Computer Laboratory in selecting the best laboratory assistant